Trends of High-Impact Studies in Pharmacology and Pharmacy: A Cross-Sectional Study - Lingmin Chen; Yi Yang; Jin Fan; Yonggang Zhang; Yonggang Zhang; Nian Li (Frontiers Media S.A., 2021)
Objective: To investigate the trends of high-impact studies in pharmacology and pharmacy research and to provide evidence for future research in the field of pharmacology and pharmacy.Methods: A cross-sectional study was performed to understand the current status of high-impact studies (top 1%) in pharmacology and pharmacy research via InCites tool based on Web of Science Core Collection. VOSViewer software was used to visualize the results. The outcomes included development trends, countries, subject areas, research institutes, collaborative networks, and subject terms.Results: We found 4,273 high-impact (top 1%) studies between 2011 and 2020 in the field of pharmacology and pharmacy. The number of studies increased from 366 in 2011 to 510 in 2020. These studies were mainly distributed in the following Web of Science subject categories: pharmacology and pharmacy (n = 4,188); neurosciences (n = 397); chemistry, multidisciplinary (n = 359); chemistry, medicinal (n = 314); microbiology (n = 301); biotechnology and applied microbiology (n = 280). These studies were cited in 646,855 studies from more than 100 Web of Science subject categories, and studies in pharmacology pharmacy accounted for the largest share of these citations. The top three countries that contributed the highest number of studies were the United States, United Kingdom, and China. The top three institutions that contributed the highest number of studies in the United States were the University of California System, the National Institutes of Health (NIH), and Harvard University. The top research collaborative circle was from universities in the United States. The top international collaborative circle was from universities from the United States, United Kingdom, Australia, and China. The subject-term analysis indicated that cancer was still the top disease, NF-κB was the top signaling pathway, and drug-delivery and nanoparticles were the top methods.Conclusion: The high-impact studies in pharmacology and pharmacy research have grown over time. The United States, the United Kingdom, and China are the top countries that contributed the high-impact studies. Cancer is still the greatest challenge in the field of disease treatment. It calls for more international collaboration in pharmacology and pharmacy research, which will help discover novel drugs.